Does a Defensive Pseudoautotomy Mechanism Exist in the Subfamily Xenodontinae? A Study of the Genus Echinanthera - Abegg, Arthur Diesel; Gomes, Cristian Alexandro [UNESP]; Entiauspe-Neto, Omar Machado; Passos, Paulo (Soc Brasileira Herpetologia, 2020)
Pseudoautotomy is presumably a derived character within Lepidosauria and occurs in taxa that have lost the ability to perform autotomy. In general, species capable of employing pseudoautotomy as a defensive strategy against predators present a high frequency of damaged tails in series deposited in herpetological collections. We assessed data from three largely sympatric Echinanthera species in the Brazilian Atlantic Rainforest (E. cephalostriata, E. cyanopleura, and E. undulata) to test previous assumptions that species of Echinanthera use their tails defensively. This hypothesis derives from anecdotal observations during fieldwork and is reinforced by the number of specimens presenting tail breakage in scientific collections. In general, the frequency of damaged tails in these species resembles that of others in which pseudoautotomy has been demonstrated. Statistical analyses revealed no differences in tail breakage frequencies between sexes for the analyzed species or between the two geographical groups defined for E. cyanopleura. In contrast, we detected a significant difference between snout-vent length and sex regarding pseudoautotomy probability for E. cyanopleura, with a positive relationship between tail breakage frequency and snout-vent length.
Keywords: Atlantic Rainforest; Defensive behavior; Echinantherini; Predation; Urotomy